Juvenile aggressive ossifying fibroma of the maxilla - Shekhar M; Bokhari K (Wolters Kluwer Medknow Publications, 2009)
Juvenile aggressive ossifying fibroma is an uncommon and controversial, benign but aggressive osteogenic neoplasm of the jaws commonly occurring in children and young adults. Complete removal of the tumor at the earliest possible stage is recommended owing to its high recurrence rate of 30-58%. Reported here is a case of recurrent juvenile aggressive ossifying fibroma of the maxilla in a 15-year-old male treated with enucleation and curettage. A 10-month follow-up showed no signs of recurrence.